Ferrous Iron Up-regulation in Fibroblasts of Patients with Beta Propeller Protein-Associated Neurodegeneration (BPAN) - Ingrassia, Rosaria; Memo, Maurizio; Garavaglia, Barbara (Frontiers in Genetics, 2017)
Mutations in WDR45 gene, coding for a beta-propeller protein, have been found in patients affected by Neurodegeneration with Brain Iron Accumulation, NBIA5 (also known as BPAN). BPAN is a movement disorder with Non Transferrin Bound Iron (NTBI) accumulation in the basal ganglia as common hallmark between NBIA classes (Hayflick et al., 2013). WDR45 has been predicted to have a role in autophagy, while the impairment of iron metabolism in the different NBIA subclasses has not currently been clarified. We found the up-regulation of the ferrous iron transporter (-)IRE/Divalent Metal Transporter1 and down-regulation of Transferrin receptor in the fibroblasts of two BPAN affected patients with splicing mutations 235+1G>A (BPAN1) and 517_519Val 173 (BPAN2). The BPAN patients showed a concomitant increase of intracellular ferrous iron after starvation. An altered pattern of iron transporters with iron overload is highlighted in BPAN human fibroblasts, supporting for a role of DMT1 in NBIA. We here present a novel element, about iron accumulation, to the existing knowledge in field of NBIA. Attention is focused to a starvation-dependent iron overload, possibly accounting for iron accumulation in the basal ganglia. Further investigation could clarify iron regulation in BPAN.